Macro-Micro Failure Mechanisms and Damage Modeling of a Bolted Rock Joint - Gang Wang; Yongzheng Zhang; Yujing Jiang; Shugang Wang; Wenjun Jing (Advances in Materials Science and Engineering)
The anchoring mechanism of a bolted joint subjected to a shear load was investigated using a bilinear constitutive model via the inner-embedded FISH language of particle flow code based on the discrete element method. The influences of the anchoring system on the macro-/micromechanical response were studied by varying the inclination angle of the bolt. The results indicate a clear relationship between the mechanical response of a bolted rock joint and the mechanical properties of the anchoring angle. By optimizing the anchorage angle, the peak strength can be increased by nearly 50% relative to that at an anchorage angle of 90°. The optimal anchorage angle ranges from 45° to 75°. The damage mechanism at the optimal anchorage angle joint is revealed from a macroscopic mechanical perspective. The concentration of the contact force between disks will appear in the joint and around the bolt, resulting in crack initiation. These cracks are mainly tensile cracks, which are consistent with the formation mechanism for compression-induced tensile cracks. Therefore, the macroscopic peak shear stress in the joint and the microscopic damage to the anchoring system should be considered when determining the optimal anchoring angle to reinforce a jointed rock mass.